ANALISIS PENGARUH KEBIJAKAN MONETER DAN KEBIJAKAN FISKAL REGIONAL TERHADAP STABILITAS HARGA DAN PERTUMBUHAN EKONOMI DI JAWA TENGAH (PERIODE 2001-2010) - Nurul Izzah Lubis (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
Inflation and economic growth is macroeconomic indicators that used to glance the condition of economy. Low inflation will have positif impact on the economy. Some empirical studies evidence that economic growth can be achieved if the inflation is low. The purpose this study is to analyze the effect of monetary policy and regional fiscal policy toward price stability and economic growth in Central Java in 2001-2010. The approach used in this study is fixed effect model (FEM).The results of this study is : (1) in partial, taxes and deposits have a significant influence on inflation, while capital expenditure, credit, interest, Banyumas, Semarang and Surakarta has not significant influence on inflation. (2) in partial, capital expenditure, credit, Banyumas and Tegal have a significant influence on economic growth, while taxes, deposits, interest, Semarangdoes not have significant influence on economic growth.The conclusion is the rapport variables used in inflation model and economic growth model according to the theory. But, the influence of each variable is not strong in inflation model and economic growth model. For the government, inflation should be controlled effectively to get a low inflation so that regional economic growth can be realized.